A Phytochemical and Ethnopharmacological Recapitulation on Hamelia patens - Noor, Gazala; Ahmad, Md.Afroz; Ahsan, Farogh; Mahmood, Tarique; Arif, Muhammad; Khushtar, Mohammad (Drug Research, 2020)
The world health organization reports that 80% of the population living within the developing countries depends basically on traditional medicine for his or her primary health care. Quite half the entire world's population still depends entirely on plants for medicines, and plants provides the active ingredients to the most traditional medical products. Hamelia patens that belong to the family Rubiaceae, is mainly found in tropical and sub-tropical areas. It is used in folk medicine against a wide range of diseases such as athlete’s foot, skin problems, insect sting, psychiatric disorder, rheumatism, headache, asthma, dysentery, menses, ovarian and uterine disorders. Hamelia consists of an important bioactive constituent such as oxindole alkaloids, flavonoids, and phenolic content. Due to the presence of chlorogenic acid and epicatechin constituent in the methanolic extract of Hamelia patens, there is a noticeable anti-hyperglycemic activity as well as it possesses antioxidant activity. Acute and sub-acute toxicity study has been performed on Hamelia patens which shows that it is safe and can be used for humans. Against fungi and bacteria, the ethanol leaf extract of Hamelia has a maximum inhibitory effect. The plant has various therapeutic effects like anti-inflammatory, analgesic, anti-diarrheal, anthelmintic, antidepressant, hepatoprotective, antiurolithiatic, diuretic, wound healing, and many others. In this article, we have discussed chemical constituent, pharmacological activity and traditional use of Hamelia patens.
Keywords: Hamelia patens; chemical constituent; pharmacological property; traditional use